White-naped squirrels use plastic waste for nest construction in agricultural areas of northern Peru. Issue 4 (4th July 2022) - Ayala, Félix; Lajo-Salazar, Leticia; Cárdenas-Alayza, Susana
ABSTRACT: The undesirable presence of plastic wastes in the marine environment is well known. Reports of effects of plastic wastes on inland continental species are very rare. This report concerns the use of plastic waste by the white-naped squirrel ( Simosciurus nebouxii ) in agricultural areas of northern Peru. Among the residues observed, single-use plastic bags were prominent. The proximity of solid waste accumulations to all the nests probably may explain why such debris was chosen, except that other nests nearby did not contain plastics. Future studies are recommended to understand the consequences for terrestrial continental fauna of using such materials.